2020
DOI: 10.1109/jssc.2020.2973639
|View full text |Cite
|
Sign up to set email alerts
|

High-Value Tunable Pseudo-Resistors Design

Abstract: Pseudo-resistor circuits are used to mimic large value resistors and base their success on the reduction of occupied areas with respect to physical devices of equal value. This article presents an optimized architecture of pseudo-resistor, made in standard CMOS 0.35 µm technology to bias a low-noise transimpedance amplifier for high-sensitivity applications in the frequency range 100 kHz-10 MHz. The architecture was selected after a critical review of the different topologies to implement high-value resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…The series connection is useful when large resistance values for wide voltage ranges are needed. Some applications require tunable pseudo-resistors, where tuning can be achieved using a DC voltage [8,12] or a DC current [13], as shown in Figure 3. Further details and examples of pseudo-resistors can be found in [8].…”
Section: Wideband Capacitive Coupling Using Quasi-floating Gate Transmentioning
confidence: 99%
See 2 more Smart Citations
“…The series connection is useful when large resistance values for wide voltage ranges are needed. Some applications require tunable pseudo-resistors, where tuning can be achieved using a DC voltage [8,12] or a DC current [13], as shown in Figure 3. Further details and examples of pseudo-resistors can be found in [8].…”
Section: Wideband Capacitive Coupling Using Quasi-floating Gate Transmentioning
confidence: 99%
“…Some applications require tunable pseudo-resistors, where tuning can be achieved using a DC voltage [8,12] or a DC current [13], as shown in Figure 3. Further details and examples of pseudo-resistors can be found in [8]. The simplest pseudo-resistor is a diode-connected PMOS transistor operating in deep subthreshold, as shown in Figure 2a [5,35,36].…”
Section: Application Of Qfg Transistors To Energy-efficient Amplifiermentioning
confidence: 99%
See 1 more Smart Citation
“…The pseudoresistor R pr was obtained by using a pair of back-toback diode connected nMOS, with the bulk short-circuited to the source, to ensure very low injection of noise and symmetric behavior for both positive and negative dc currents [5]. Since the pseudoresistor is made by MOS transistors operating in subthreshold, its equivalent small signal resistance R pr changes with the dc input current I DC , according to the relation R pr = n • V th /I DC , where V th is the thermal voltage and n ≈ 1.5 is the subthreshold coefficient.…”
Section: A Active DC Handling Networkmentioning
confidence: 99%
“…In order to achieve the cut off of 0.1 Hz, the required value of the resistance is 1G-ohm. The controlled pseudo MOSFET resistance is used herein to realize the high value resistance (Guglielmi et al 2020 ; Shiue et al 2011 ). The circuit diagram of the pseudo resistance used in this study is shown in Fig.…”
Section: Design Of Ppg Signal Acquisition Sensor and Systemmentioning
confidence: 99%